METHOD OF DEVELOPING STUDENTS' SENSE OF ENGAGEMENT IN HISTORY THROUGH COGNITIVE-REFLECTION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article describes the essence, purpose, significance of the development of a sense of involvement in history in students of education using the cognitive-reflexive method and a set of pedagogical views related to the supreme law. , its production processes, integration processes into the educational process and educational processes, educational processes. In addition, this research work provides proposals for cognitively ensuring a sense of involvement in history in students.